AIRPORT RAMP RISK ANALYSIS AT HALIM PERDANAKUSUMA - Mustika Sari; Dian Artanti Arubusman; Syaiful Abbas (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2015)
In the last ten years airline industry has grown rapidly and has made airport ramp or apron busier with its activities. The work time in this area is relatively short, causing the work pressure higher than other areas. It is not surprising that accidents and incidents are more potential to happen here. By identifying the hazard and risk, and then doing a risk analysis, the level of risk can be known using a qualitative method referring to the Australian/New Zealand Standard or AS/NZS 4360:2004. It is clear that the highest risks of ramp activities are noise, being struck by operational vehicles, and being squeezed by GSE equipment. Meanwhile, the activities with high risk include fatique, dust, being squeezed by hydraulic during preparation, being scratched by iron, improper body position when putting mannual GSE, being struck down by things, falling down, and getting lavatory water splashed on.